(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The production of a clasp prosthesis with a locking type of fixation for prosthetics of partial defects in the dentition is the most functional and aesthetic. Clasp dentures are used: when there is an insufficient number of supporting teeth for the manufacture of fixed dentures; the presence of supporting teeth with insufficient periodontal reserve forces, with varying degrees of periodontal atrophy; unilateral and bilateral distally not limited defects of the dentition.